European Union Social Policy as an Instrument for Sustainable Development; Polityka społeczna Unii Europejskiej jako instrument zroẃnowazȯnego rozwoju - Janina Witkowska (Comparative Economic Research. Central and Eastern Europe, 2010)
This paper undertakes an analysis and assessment of European Union (EU) social policy in the context of the sustainability of the group's social and economic development. The process of Europeanizing EU social policy is not advanced. Thus, the weight of solving social problems primarily rests with member countries. EU social policy is "looser" in character than other EU policies and its scope is limited to those areas where member states were willing to transfer certain prerogatives to European Union level. The EU only supports social policy in the context of the sustainability of the group's social and economic development. The process of Europeanizing EU social policy is not and supplements the actions of member states in the social sphere. At the same time, the EU supports the concept of corporate social responsibility. Corporate social responsibility is defined as the voluntary taking into account by companies of social and environmental matters in their operations and in relations with interested parties. – – W artykule została przeprowadzona analiza i ocena polityki społecznej Unii Europejskiej (UE), w konteksćie roẃnowazėnia rozwoju społeczno-gospodarczego ugrupowania. Proces europeizacji polityki społecznej UE nie jest zaawansowany. W zwiazku z tym, ciezȧr rozwiazywania problemoẃ społecznych spoczywa głoẃnie na krajach członkowskich. Polityka społeczna UE ma bardziej "luzńy" charakter nizi̇nne polityki UE i jej zakres jest ograniczony do tych dziedzin, w zakresie ktoŕych kraje członkowskie były skłonne do przekazania pewnych uprawnienńa szczebel unijny. UE jedynie wspiera i uzupełnia działania panśtw członkowskich w sferze społecznej. Jednoczesńie UE wspiera idee społecznej odpowiedzialnosći przedsiebiorstw. Społeczna odpowiedzialnosćṕrzedsiebiorstw definiuje sie jako dobrowolne uwzglednienie przez przedsiebiorstwa problematyki społecznej i ekologicznej w swojej działalnosći i stosunkach z zainteresowanymi stronami.
Keywords: 330